Acute and Long-Term Treatment With Dapagliflozin and Association With Serum Soluble Urokinase Plasminogen Activator Receptor - Viktor Rotbain Curovic; Morten B. Houlind; Tine W. Hansen; Jesper Eugen-Olsen; Jens Christian Laursen; Mie K. Eickhoff; Frederik Persson; Peter Rossing; Peter Rossing (Frontiers Media S.A., 2022)
Background: Elevated soluble urokinase plasminogen activator receptor (suPAR) is highly associated with increased risk of diabetic complications. Dapagliflozin is a drug inhibiting the sodium-glucose co-transporter 2 in the kidney to decrease blood glucose, while also decreasing risk of kidney disease, heart failure, and death. Therefore, we have investigated suPAR as a monitor for treatment effect with dapagliflozin in diabetes.Methods: suPAR was measured in two double-blinded randomized clinical cross-over trials. The first trial investigated the effect of a single dose dapagliflozin 50 mg or placebo 12 h after intake, in individuals with type 1 diabetes and albuminuria. The second trial investigated the effect of a daily dose dapagliflozin 10 mg or placebo for 12 weeks, in individuals with type 2 diabetes and albuminuria. suPAR was measured in serum samples taken, in the acute trial, after treatment with dapagliflozin and placebo, and in the long-term trial, before and after treatment with dapagliflozin and placebo. Effect of dapagliflozin on suPAR levels were assessed using paired t-test.Results: 15 participants completed the acute trial and 35 completed the long-term trial. Mean difference in suPAR between dapagliflozin and placebo in the acute trial after 12 h was 0.70 ng/ml (95% CI: 0.66; 1.33, p = 0.49). In the long-term trial the mean difference was 0.06 ng/ml (95% CI -0.15; 0.27, p = 0.57).Conclusion: Based on our findings we conclude that suPAR is not a feasible marker to monitor the effect of treatment with dapagliflozin. Thus, a further search of suitable markers must continue.